Long-Term Blood Pressure Variability and Kidney Function in Participants of the ASPREE Trial. (14th September 2021) - Ernst, Michael E; Fravel, Michelle A; Webb, Katherine L; Wetmore, James B; Wolfe, Rory; Chowdhury, Enayet; Reid, Christopher M; Woods, Robyn L; Beilin, Lawrence; Margolis, Karen L; Murray, Anne M; Polkinghorne, Kevan R
Abstract: Background: Whether long-term blood pressure variability (BPV) predicts kidney function decline in generally healthy older adults is unknown. We investigated this association in ASPirin in Reducing Events in the Elderly (ASPREE) trial participants. Methods: Between 2010 and 2014, Australian and US individuals aged ≥70 years (≥65 if US minority) were recruited and followed with annual study visits for a median of 4.7 years. Time-to-event analyses and linear mixed effects models were used to examine associations between incident chronic kidney disease (CKD), and trajectories of estimated glomerular filtration rate (eGFR) and log albumin–creatinine ratio (log ACR) with systolic BPV as a continuous measure, and, by tertile of SD of systolic blood pressure (BP). BPV was estimated using systolic BP measures from baseline through the second annual visit, and kidney outcomes were assessed following this period. Results: Incident CKD occurred in 1, 829 of 6, 759 participants (27.2%), and more commonly in BPV tertiles 2 (27.4%) and 3 (28.3%) than tertile 1 (25.5%); however, the risk was not significantly increased after covariate adjustment (tertile 3 hazard ratio = 1.02; 95% confidence interval: 0.91–1.14). Analysis of eGFR ( n = 16, 193) and log ACR trajectories ( n = 15, 213) showed individuals in the highest BPV tertile having the lowest eGFR and highest log ACR, cross-sectionally. However, the trajectories of eGFR and log ACR did not differ across BPV tertiles. Conclusions: CKD and markers of reduced kidney function occur more commonly in individuals with higher BPV; however, BPV does not influence trajectory of decline in kidney function over time in older adults who are in generally good health. Clinical trials registration: Trial Number NCT01038583 and ISRCTN83772183. Graphical Abstract: